Three zone modeling of downdraft biomass gasification : equilibrium and finite kinetic approach - Budhathoki, Roshan (2013)
Mathematical models and simulations are being practiced exceedingly in the field of research and development work. Simulations provide a less expensive means of evaluating the benefits and associated risk with applied field. Gasification is a complex mechanism, which incorporates thermochemical conversion of carbon based feedstock. Therefore, simulation of gasification provides a better comprehension of physical and chemical mechanism inside the gasifier than general conjecture and assist in optimizing the yield. The main objectives of present thesis work involve formulation of separate sub-model for pyrolysis and oxidation zone from published scientific references, and assembling it with provided existing irresolute model of reduction zone to establish a robust mathematical model for downdraft gasifier. The pyrolysis and oxidation zone is modeled with equilibrium approach, while the reduction zone is based on finite kinetic approach. The results from the model are validated qualitatively against the published experimental data for downdraft gasifier. The composition of product gas has been predicted with an accuracy of ~92%. Furthermore, the precision in temperature prediction assists the gasifier designer for proper selection of material, while precision in gas composition prediction helps to optimize the gasification process. Lower moisture content in the biomass and equivalence ratio lower than 0.45 are proposed as optimal parameters for downdraft gasification of woody biomass. However, the model is found to be incompetent for prediction of the gas composition at higher equivalence ratio. Thus, due to several uncertainties and incompetence of present model at higher equivalence ratio, further need of development of model has been propounded.